Ethical Governance in a Digitally Driven World: Leadership at the Intersection of Innovation, Risk, and Human Responsibility - Bunic, Indira (Global journal of Business and Integral Security, 2026)
Digital technologies, AI, big data, cloud computing, and always-on connectivity are reshaping social and economic systems, introducing non-trivial ethical risks, ranging from bias and privacy harms to inequities and disinformation. This paper focuses on ethical governance as a leadership practice that aligns innovation with risk oversight and human responsibility. Drawing on recent regulatory developments (e.g., the EU AI Act and the UAE AI Charter), corporate governance shifts (e.g., Chief AI Officer roles), and digital ethics scholarship, it proposes a practical framework that integrates ethicsby- design, risk oversight, and rights-based leadership across the AI lifecycle. Using a qualitative normative synthesis with illustrative cases, the paper outlines actionable steps for boards and leaders, focusing on structures, decision-making, documentation, assurance, stakeholder engagement, and postdeployment monitoring. We argue that ethical governance is not a brake on innovation but the operating discipline that enables trustworthy systems, resilient organizations, and outcomes worthy of those they serve.